Deliberating Collective Decisions - Chan, Jimmy; Lizzeri, Alessandro; Suen, Wing; Yariv, Leeat (Review of Economic Studies, 2018)
We present a dynamic model of sequential information acquisition by a heterogeneous committee. At each date, agents decide whether to vote to adopt one of two alternatives or continue to collect more information. The process stops when a qualified majority vote for an alternative. Three main insights emerge from our analysis and are consistent with an array of stylized facts regarding committee decision making. First, majority rule is more vulnerable than super-majority rules to the disproportionate influence of impatient committee members. Second, more diverse preferences, more patient members, or more unanimous decision voting rules lead to lengthier deliberation and more accurate decisions. Finally, balanced committees unanimously prefer to delegate deliberation power to a moderate chairman rather than be governed by a rule such as unanimity.